Senzorična stimulacija v procesu ponovnega učenja gibanja pri odraslih po nezgodni poškodbi možganov - Povše, Maja (Rehabilitacija (Ljubljana), 2012)
Patient after traumatic brain injury often have problems with sensory processing. Their central nervous system is not processing the sensory stimulus in the same way as before the brain injury. Because of that, the function and the behaviour of the patient can change. Patients after traumatic brain injury either do not receive enough sensory information because of movement disorders, or they cannot properly react to the stimuli - often they cannot understand what is happening around them, what they see, feel, hear etc. For evoking movement and improving the process of perception and learning, sensory stimulation can be used in such patients, which supplements other techniques and methods of physiotherapy. With sensory stimulation, we try to provide appropriate sensory input to the patient and facilitate his/her active participation in the process of motor relearning.
Keywords: gibanje; motnje; Movement; možgani; Nervous System; Perception; poškodbe; sensory integration; sensory stimulation; senzorična integracija; senzorična stimulacija; zaznavanje; živčevje